The contaminated incubator as a cause of Aspergillus fumigatus infection of chick embryos - Brada, Wilhelm (Pesquisa Agropecuaria Brasileira, 2014)
Experiments with by Aspergillus fumigatus contaminated incubator were made. The author obtained easily embryos infected and was able to isolate the fungus. A desinfection of the incubator with 2% formalin performed twice, was not sufficient to avoid completely the infection.